American Abstract Artists - American Abstract Artists (2008)
[Dt.:] Vereinigung von abstrakten Künstlern aus Nordamerika; Informationen zur Organisation; Interviews mit Künstlern; Ausstellungsverzeichnis. [Engl.:] Association of North American abstract artists; information on the organisation; interviews with artists; exhibition archive (lists).